2021
DOI: 10.3390/pathogens10081015
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Psittaci ST24: Clonal Strains of One Health Importance Dominate in Australian Horse, Bird and Human Infections

Abstract: Chlamydia psittaci is traditionally regarded as a globally distributed avian pathogen that can cause zoonotic spill-over. Molecular research has identified an extended global host range and significant genetic diversity. However, Australia has reported a reduced host range (avian, horse, and human) with a dominance of clonal strains, denoted ST24. To better understand the widespread of this strain type in Australia, multilocus sequence typing (MLST) and ompA genotyping were applied on samples from a range of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(50 citation statements)
references
References 47 publications
(95 reference statements)
4
46
0
Order By: Relevance
“…psittaci is considered to have the broadest host range amongst all Chlamydiaceae, highlighting its effectiveness in infecting genetically diverse hosts, including humans and causing zoonotic disease (Borel et al, 2018;Knittler & Sachse, 2015;Radomski et al, 2016). Prelimi-nary strain characterization using ompA genotyping from five parrots, an Australian bustard, masked lapwing and sacred kingfisher from this study revealed ompA genotype A, commonly detected in highly virulent, clonal, globally distributed psittacine, livestock and human ST24type strains (Anstey et al, 2021;Vorimore et al, 2021) (Figure 5a).…”
Section: Psittaci Was Detected In Expanded Avian Host Rangementioning
confidence: 75%
See 2 more Smart Citations
“…psittaci is considered to have the broadest host range amongst all Chlamydiaceae, highlighting its effectiveness in infecting genetically diverse hosts, including humans and causing zoonotic disease (Borel et al, 2018;Knittler & Sachse, 2015;Radomski et al, 2016). Prelimi-nary strain characterization using ompA genotyping from five parrots, an Australian bustard, masked lapwing and sacred kingfisher from this study revealed ompA genotype A, commonly detected in highly virulent, clonal, globally distributed psittacine, livestock and human ST24type strains (Anstey et al, 2021;Vorimore et al, 2021) (Figure 5a).…”
Section: Psittaci Was Detected In Expanded Avian Host Rangementioning
confidence: 75%
“…These findings indicate that the Australian avian host range of C. psittaci is grossly underestimated (Anstey et al., 2021; Stokes et al., 2021, 2020; Sutherland et al., 2019). Furthermore, these infections were only described in a handful of surveillance studies conducted in one distinct Australian region, in the state of Victoria (Amery‐Gale et al., 2020; Stokes et al., 2019, 2020; Sutherland et al., 2019) or as a discrete part of genotyping or equine/human infection studies (Anstey et al., 2021; Branley et al., 2016; Jelocnik et al., 2017; Jenkins et al., 2018). Regarding other avian chlamydial species in Australia, to date, only a single report describes C. gallinaceae in free‐range chickens and a single wild galah (Stokes et al., 2019), starkly contrasting global avian chlamydial species and host diversity.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The prevalence and role of the Chlamydiaceae in sympatric wild and domesticated animals is also of interest due to the potential for cross-host infections [ 17 ]. Specifically, a study investigating mountain habitats in northern Spain showed that 0.6% of the free-range Pyrenean chamois ( Rupicapra pyrenaica ) and 1.4% of the domestic sheep, from a total of 893 animals evaluated, were positive for Chlamydiaceae , with C. pecorum being the only species identified.…”
Section: Chlamydial Infections In Wildlife: Concerns For Spill-over A...mentioning
confidence: 99%
“…These ST24/ omp A genotype A strains pose a documented zoonotic risk to humans. The authors further discovered a novel strain (ST306) in the Western brush wallaby, a novel host of C. psittaci [ 17 ]. The multidisciplinary approach in this study ranging from equine infectious disease to ecology is in line with the “One Health” perspective [ 21 ].…”
Section: Chlamydial Infections In Wildlife: Concerns For Spill-over A...mentioning
confidence: 99%